Poetry of Marina Tsvetaevoi (Zien Journal of Social Sciences and Humanities, 2022)
This article is dedicated to Marina Tsvetaeva and her inexhaustible poetry in Russian and world literature, she is like a Russian poetess, proseand translator, of which she isone of the largest representatives and poets of the Silver Age of Russian literature. The poem "Homesickness" is analyzed!